Effect of Carbon Performance, Company Characteristics and Environmental Performance on Carbon Emission Disclosure: Evidence from Indonesia - Ratmono, Dwi; Darsono, Darsono; Selviana, Selviana (International Journal of Energy Economics and Policy, 2020)
This study aims to examine and obtain empirical evidence of the factors that influence the disclosure of carbon emissions in public listed companies in Indonesia. The factors tested include carbon performance, firm size, profitability, leverage, capital expenditure, the level of asymmetry of company information and environmental performance. The population in this study are companies listed on the Indonesia Stock Exchange. The sample selection method uses a purposive sampling method, namely sampling based on criteria: publishing annual reports and sustainability reports in 2013 - 2017 and disclosing carbon emissions explicitly. The final sample in this study were 9 companies. The results showed that company size and capital expenditure had a positive and significant effect on carbon emission disclosure. Meanwhile, profitability and leverage have a negative and significant effect. The results also showed that carbon performance, the level of information asymmetry and environmental performance did not significantly influence the disclosure of carbon emissions. Keywords: Carbon Emissions Disclosure, Carbon Performance, Environmental Disclosures, Environmental Performance JEL Classifications: Q51, Q56, M41 DOI: https://doi.org/10.32479/ijeep.10456